Hensel's Lemma:

Let $F(x)=\alpha_0 + \alpha_1 x+ \dots + \alpha_n x^n \in \mathbb{Z}_p[x]$.

We suppose that there is a $p$-adic $a_1 \in \mathbb{Z}_p$ such that

$$F(a_1) \equiv 0 \mod p \mathbb{Z}_p \\ \text{ and } F'(a_1) \not\equiv 0 \mod p \mathbb{Z}_p$$

Then, $\exists\alpha \in \mathbb{Z}_p$ such that $F(\alpha)=0$.

The proof is the following:

We will prove the existence of a root $a$ n $\mathbb{Z}_p$, constructing a Cauchy sequence, $a_1, a_2, \dots $ that converges to $\alpha$.

For each $n \geq 1$, we will construct $a_n$ such that

  1. $F(a_n) \equiv 0 \mod p^n \mathbb{Z}_p$
  2. $a_n \equiv a_{n+1} \pmod {p^n}$

for $a_2$

$F(a_2) \equiv 0 \mod p^2 \mathbb{Z}_p$

and $a_1 \equiv a_2 \pmod p$

$a_1 \equiv a_2 \pmod p \Rightarrow a_2=a_1+p b_1 \ | \ b_1 \in \mathbb{Z}_p$

So, $F(a_2)=F(a_1+pb_1) \overset{ \text{ Taylor }}{ = }F(a_1)+F'(a_1) \cdot b_1 \cdot p+ (\text{ terms in } p^n \mathbb{Z}_p, \text{ for } n \geq 2 )$

We want $F(a_2) \equiv 0 \pmod {p^2 \mathbb{Z}_p}$.

So, it should be $F(a_1)+F'(a_1) \cdot b_1 \cdot p \equiv 0 \pmod {p^2}$

From the hypothesis we have that $F(a_1)=p \cdot x$, so $p\cdot x+F'(a_1)\cdot b_1 \cdot p \equiv 0 \pmod {p^2}$

$\Rightarrow x+F'(a_0=1) \cdot b_1 \equiv 0 \pmod p$

$\Rightarrow F'(a_1)\cdot b_1 \equiv (-x) \pmod p$

Since $F'(a_1) \not\equiv 0 \pmod {p \mathbb{Z}_p}$, we have that the congruence has an unique solution

$b_1=(-x)[F'(a_1)]^{-1} \pmod p$

So, we calculated $a_2$.

Similarily, $a_n$ and so on.

So, we constructed a sequence $$a_1, a_2, \dots , a_n, a_{n+1}, \dots $$ where $a_n \equiv a_{n+1} \pmod {p^n}, \forall n \in \mathbb{N}$.

So, $a_{n+1}-a_n=p^n \cdot k \Rightarrow |a_{n+1}-a_n|_p \leq \frac{1}{p^n}$

$\lim_{n \rightarrow \infty} |a_{n+1}-a_n|_p=0$

$\Rightarrow \{a_n\}$ Cauchy

So, it converges, i.e.

$$\lim_{n \rightarrow \infty} a_n=\alpha$$

(By continuity of the polynomial function $F(x)$ we have that $F(\alpha)=0$)

Also $a_1 \equiv \alpha \pmod {p \mathbb{Z}_p}$, from the construction of $\alpha$.

  1. Could you explain to me why at the beginning we construct $a_n$ for each $n \geq 1$ such that

    1. $F(a_n) \equiv 0\mod p^n \mathbb{Z}_p$
    2. $a_n \equiv a_{n+1} \pmod {p^n}$
  2. At $$a_1 \equiv a_2 \pmod p \Rightarrow a_2=a_1+p b_1 \ | \ b_1 \in \mathbb{Z}_p$$ why is $b_1 \in \mathbb{Z}_p$ and not $b_1 \in > \mathbb{Z}$?


1 Answer 1


$1.1$ We need that the solutions continue to be congruent to $0\mod p^n\Bbb Z_p$ because we are using the fact that the values converge to $\Bbb 0$ in $\Bbb Z_p$. Recall that $|x|_p=0\iff x=0$, so that the only number which is $\equiv 0\mod p^n$ for every $n$ is $0$ itself.

$1.2$ The point of constructing the sequence so that the reductions modulo $p^n$ have that property is reflected in the structure of the $p$-adic integers.

Note that a $p$-adic integer is formally a sum

$$\sum_{n=0}^\infty a_np^n,\quad 0\le a_n\le p-1$$

So the integers $a_0, a_0+a_1p, a_0+a_1p+a_2p^2,\ldots$ uniquely determine the $p$-adic integer just as does the sequence $3, 3.1, 3.14, 3.141,\ldots$ determines $\pi$. This means that a solution in $\Bbb Z_p$ is equivalent to a solution modulo $p^n$ for every $n$, which reduces down properly modulo all the lower powers. If your prime is say $3$ and your first candidate solution modulo $3$ is say $a_0=1$, but your second solution is $5=2+1\cdot 3^1$, then you have shifted your $3$-adic answer, it's no longer possible that these represent the same $3$-adic number as the sequence goes on, because any difference in the digits, changes the number, just like, $3.12\ldots$ cannot be $\pi$, no matter what comes after the $2$, because once you differ in one digit you are forever different.

$2$. Because in $\Bbb Z_p$ you have more options than you did in $\Bbb Z$. It might help to go back to definitions:

$$a\equiv b\mod p\iff a-b=pk$$

what ring $k$ comes from depends on your context, it is only classically that the symbol $\text{mod}$ has been used for integers, if you remember some of your ring theory, quotient rings are often written as $a\equiv b\mod I$ for some ideal $I$ when the two elements $a,b$ have the same image in the quotient ring, $R/I$. Here in this proof they are using that $p\Bbb Z_p$ is an ideal in $\Bbb Z_p$ and mean the terminology $\mod p$ to mean modulo the ideal $p\Bbb Z_p$. The writers are taking a notational shortcut because the context is $\Bbb Z_p$, so they understand $a_1\equiv a_2\mod p$ as shorthand for

$$a_1\equiv a_2\mod p\Bbb Z_p\iff a_1=a_2pb_1,\quad b_1\in\Bbb Z_p.$$

  • $\begingroup$ Thank you for your answer... I will read it in a little while...Before I have also an other question... At the proof at the part: "For each $n \geq 1$, we will construct $a_n$ such that $$ 1. F(a_n) \equiv 0 \mod p^n \mathbb{Z}_p$$ $$ 2. a_n \equiv a_{n+1} \pmod {p^n}$$ for $a_2$ $F(a_2) \equiv 0 \mod p^2 \mathbb{Z}_p$ and $a_1 \equiv a_2 \pmod p$ " at the general formula at the second identity for $n=2$ (since at the first identity we used $n=2$) we get $a_2 \equiv a_{3} \pmod {p^2}$ but we have $a_1 \equiv a_2 \pmod p$... So, is the general formula wrong?? $\endgroup$
    – Mary Star
    Jan 29, 2015 at 21:57
  • $\begingroup$ Ah, no, that's not a problem: a typical example here is $p=5$, $a_0=1, a_1 = 6, a_2 =56$. Note that $a_2\equiv a_1\mod p^2$ and also $a_1\equiv a_0\mod p$, there's no contradiction, they're just noting that $a\equiv b\mod p^n\implies a\equiv b\mod p^m$ for any $m\le n$. $\endgroup$ Jan 29, 2015 at 21:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.